Randomized multicenter phase II trial of prophylactic irradiation of para‐aortic lymph nodes in advanced cervical cancer according to tumor hypoxia: Korean Radiation Oncology Group (KROG 07‐01) study. Issue 12 (11th July 2022) - Yoon, Meesun; Lee, Hyo Kyung; Park, Eun Young; Kim, Jin Hee; Lee, Jong Hoon; Kim, Young Seok; Kim, Hak Jae; Kim, Hunjung; Yoo, Chong Woo; Lee, Sun; Hong, Eun Kyung; Kim, Tae Hyun; et al.
Abstract: We conducted a prospective phase II study on whether extended‐field irradiation (EFI) confers survival benefits depending on hypoxic markers in locally advanced uterine cervical cancer (LAUCC). RNA‐seq was performed to identify immune and hypoxic gene signatures. A total of 288 patients were randomized to either EFI or pelvic radiotherapy (PRT). All patients completed chemoradiotherapy. Overall, significantly higher 5‐year para‐aortic recurrence free survival (PARFS) rate occurred in EFI (97.6%) than in PRT group (87.2%), with marginal tendency to improve disease‐free survival (DFS; 78% vs 70%, P  = .066). Subgroup analyses were performed based on carbonic anhydrase 9 (CA9)‐only positive, CA9/hypoxia‐inducible factor (HIF) double positive and CA9 negative. In the CA9‐only positive, EFI successfully increased 5‐year PARFS (100% vs 76.4%, P  = .010), resulting in significantly improved long‐term DFS (85.7% vs 54.7%, P  = .023) compared to the PRT, while there was no such benefit of EFI in the CA9/HIFs double positive. RNA‐seq analysis identified distinct immune high subgroup with negative correlation with hypoxia gene signatures ( R  = −.37, P  < .01), which showed a higher 5‐year DFS than the immune low ( P  = .032). Hypoxia‐related genes were upregulated in the CA9/HIFs double positive compared to CA9 negative ( P  < .05). Only 17.4% of patients in CA9‐negative group showed immune low signatures, while 40.0% of patients in the double‐positive group exhibited immune low signatures. In conclusion, EFI improved PARFS significantly in all patients, but therapeutic efficacy of EFI in terms of improved DFS was solely observed in CA9‐only positive LAUCC, and not in CA9/HIFs double‐positive subgroup. RNA‐seq analysis suggested that hypoxia‐induced immunosuppression may be related to treatment resistance in LAUCC. Abstract : What's new? Prophylactic extended‐field irradiation (EFI) to the para‐aortic lymph nodes (PAN) has been shown to decrease the incidence of PAN metastasis in advanced cervical cancer. However, it is unclear whether prevention of PAN metastasis translates into improved survival rates. In this prospective phase II study, EFI improved PAN recurrence‐free survival in all patients compared to pelvic radiotherapy, but therapeutic efficacy in terms of improved disease‐free survival was only observed in mildly‐hypoxic cases, and not in CA9 and HIF‐1α or HIF‐2α double‐positive tumors. RNA‐seq analysis suggested that hypoxia‐induced immunosuppression may be related to treatment resistance in advanced cervical cancer.